Comparative analysis of the radiation situation in the Stepnogorsk district in the Akmola region - Bagramova, А.А.; Zhumadilov, К.Ш.; Sakaguchi, А. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The territory of the Akmola region is characterized by the presence of a number of radiation factors caused by natural and man-made manifestations of increased radioactivity, the main of which are numerous areas of anomalous increases in natural radioactivity, uranium deposits and ore occurrences, as well as long-term large-scale activities of uranium mines and enterprises for the extraction of other minerals, with associated uranium mineralization. In this article, we will show the results of a study of pollution in the Stepnogorsk district in recent years and demonstrate the analysis of the data. The article will analyze the research data of 2016 and 2020. Comparison of the results showed that the concentration of pollution is present in high doses, in particular, special attention is paid to the village of Aksu.